2014
DOI: 10.5392/jkca.2014.14.10.255
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Affective Commitment in Explaining Relationship between Characteristics of Service-offer and Loyalty: Focused on Department Stores

Abstract: This study confirmed structural causal relations among concepts such as characteristics of service-offer, satisfaction, trust, affective commitment, and loyalty and surveyed mediating roles of affective commitment. The results are as follows. First, Customized service and service reliability influenced satisfaction while service competency did not. Service reliability affected trust while customized service and service competency did not. Second, satisfaction influenced trust and affective commitment but not l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Blodgett et al (1997) demonstrated that perceived distributive justice positively influences consumers' attitudes toward a firm and repatronage intentions. Choi and Huh (2014) discovered that perceived distributive justice can shape consumer loyalty through consumers' affective commitment. Consumers display higher overall satisfaction with a firm when they perceive high levels of distributive justice; they may thus develop stronger purchase intentions and word-of-mouth loyalty intentions (Fan and Du, 2008;Maxham and Netemeyer, 2002;Su and Huang, 2010).…”
Section: Cross-border Philanthropymentioning
confidence: 99%
“…Blodgett et al (1997) demonstrated that perceived distributive justice positively influences consumers' attitudes toward a firm and repatronage intentions. Choi and Huh (2014) discovered that perceived distributive justice can shape consumer loyalty through consumers' affective commitment. Consumers display higher overall satisfaction with a firm when they perceive high levels of distributive justice; they may thus develop stronger purchase intentions and word-of-mouth loyalty intentions (Fan and Du, 2008;Maxham and Netemeyer, 2002;Su and Huang, 2010).…”
Section: Cross-border Philanthropymentioning
confidence: 99%